Am I suffering from obsessive compulsive disorder? / Emily Jothee Mathai - Mathai, Emily Jothee (Academy of Language Studies, 2023)
Collecting items is an interesting hobby. Items can easily be made up of stamps, money, old memorable things such as phones, cameras etc. Apparently, accumulating items of interest sounds reasonable but having a stockpile at home so to speak that "these collectors" can't use their home for the intended purpose - becomes problematic. That is what we call - HOARDING. Is it normal to gather uncountable items and be classified as untidy or is it a serious disorder? According to the American Psychiatric Association (2013) people with hoarding disorder have persistent difficulty getting rid of or parting with possessions due to a perceived need to save the items. Attempts to part with possessions create considerable distress and lead to decisions to save them. The resulting clutter disrupts the ability to use living spaces.